Assembling p53 Activating Peptide With CeO2 Nanoparticle to Construct a Metallo-Organic Supermolecule Toward the Synergistic Ferroptosis of Tumor - Wang, Jingmei; Yang, Wenguang; He, Xinyuan; Zhang, Zhang; Zheng, Xiaoqiang (Frontiers in Bioengineering and Biotechnology, 2022)
Inducing lipid peroxidation and subsequent ferroptosis in cancer cells provides a potential approach for anti-cancer therapy. However, clinical translation of such therapeutic agents is often hampered by ferroptosis resistance and acquired drug tolerance in host cells. Emerging nanoplatform-based cascade engineering and ferroptosis sensitization by p53 provide a viable rescue strategy. Herein, a metallo-organic supramolecular (Nano-PMI@CeO2) towards p53 restoration and subsequent synergistic ferroptosis is constructed, in which the radical generating module-CeO2 nanoparticles act as the core, and p53-activator peptide (PMI)-gold precursor polymer is in situ reduced and assembled on the CeO2 surface as the shell. As expected, Nano-PMI@CeO2 effectively reactivated p53 signaling pathway in vitro and in vivo, thereby down-regulating its downstream gene GPX4. As a result, Nano-PMI@CeO2 significantly inhibited tumor progression in the lung cancer allograft model through the p53 restoration and the sensitized ferroptosis, while maintaining favorable biosafety. Collectively, this work develops a tumor therapeutic with dual functions of inducing ferroptosis and activating p53, demonstrating a potentially viable therapeutic paradigm for sensitizing ferroptosis via p53 activation. It also suggests that metallo-organic supramolecule holds great promise in transforming nanomedicine and treating human diseases.